Atrichia, abnormal EEG, epilepsy and mental retardation in two sisters - Richieri-Costa, A.; Frota-Pessoa, O. (Karger, 1979)
Two daughters of a nonconsanguineous couple are described. Both present mental retardation, epileptic seizures, congenital atrichia, histologically anomalous skin and abnormal EEG pattern. From a discussion of the literature on atrichia, the forms without involvement of teeth, nails and hidrosis, among which recessive inheritance prevails, are distinguished from each other. None of them coincide with the syndrome described here.
Keywords: atrichia; case report; central nervous system; congenital disorder; electroencephalography; epilepsy; heredity; inheritance; mental deficiency; school child; seizure; sibling; skin disease; child; congenital malformation; congenital skin disease; female; genetics; hair; human; multiple malformation syndrome; syndrome; Abnormalities, Multiple; Case Report; Child; Electroencephalography; Epilepsy; Female; Hair; Human; Mental Retardation; Skin Abnormalities; Syndrome